2020
DOI: 10.1017/s1049023x20000825
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical Simulants in Urine: A Useful Tool for Assessing Emergency Decontamination Efficacy in Human Volunteer Studies

Abstract: Introduction: To date, all human studies of mass-casualty decontamination for chemical incidents have relied on the collection and analysis of external samples, including skin and hair, to determine decontamination efficacy. The removal of a simulant contaminant from the surface of the body with the assumption that this translates to reduced systemic exposure and reduced risk of secondary contamination has been the main outcome measure of these studies. Some studies have investigated systemic exposure thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Another possibility is that MeS skin absorption is rapid and the 15-minute delay before commencing intervention is insufficient to influence systemic levels significantly. When MeS was examined in urine in a feasibility study using 100uL applied simulant [ 10 ] peak urine levels at 1h were significantly higher than baseline but other time points did not reach significance. Further examination of suitable MeS application dose and how to avoid MeS exposure from dietary and other sources is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is that MeS skin absorption is rapid and the 15-minute delay before commencing intervention is insufficient to influence systemic levels significantly. When MeS was examined in urine in a feasibility study using 100uL applied simulant [ 10 ] peak urine levels at 1h were significantly higher than baseline but other time points did not reach significance. Further examination of suitable MeS application dose and how to avoid MeS exposure from dietary and other sources is required.…”
Section: Discussionmentioning
confidence: 99%
“…Further examination of suitable MeS application dose and how to avoid MeS exposure from dietary and other sources is required. In addition, alternative simulant contaminants should be explored which may be more suitable for assessing systemic exposure in urine [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…foodstuffs. A subsequent study by James et al 32 measuring parent MeS in urine also suggested that exogenous sources of MeS can confound data interpretation. Whilst the MeS data in this study should be interpreted within this context both MeS and BeS concentrations in this study were much higher in control and www.nature.com/scientificreports/ intervention samples than in baseline samples indicating that a systemic effect due to dermal penetration was being observed.…”
Section: Discussionmentioning
confidence: 99%
“…MeS and BeS in hair samples and swabs were measured by gas chromatography triple quadruple mass spectrometry (GC-MS/MS) according to the method described by James et al 34,35 . MeS and BeS in 24-urine samples were measured by GC-MS/MS according to James et al 32 .…”
Section: Uv Photography and Image Analysis Uv Photography Was Conducmentioning
confidence: 99%